1985
DOI: 10.1177/0022427885022004004
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Criminality among Heroin Users

Abstract: Female crime has been explained in terms of feminist and traditional (control, cultural deviance, commitment to conventional institutions) theories. In this study, self-reported arrests were examined for 170 female and 202 male heroin users in treatment to determine if these theories differ in their capacity to account for female as opposed to male criminality. The results indicate that control theory best explains female arrests, perhaps because breakdowns in familial supervision have more devastating impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
2
39
0
1
Order By: Relevance
“…Similarly, Hirschi's [58] social bonding theory holds that girls and boys experience different familial processes and develop different types of social bonds and interpersonal relationships with family members, which are very important to girls. In this context, Covington [59] argued that problematic familiar relations may negatively influence girls more than boys, and Alarid et al [60] found that a lack of parental attachment is a more significant predictor of violent crime by women than by men.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hirschi's [58] social bonding theory holds that girls and boys experience different familial processes and develop different types of social bonds and interpersonal relationships with family members, which are very important to girls. In this context, Covington [59] argued that problematic familiar relations may negatively influence girls more than boys, and Alarid et al [60] found that a lack of parental attachment is a more significant predictor of violent crime by women than by men.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that youths who witness violence behave in gender-typical ways [43] where males are more likely than females to justify violent behaviors [44]. However, previous research has also shown that females tend to be more negatively affected by changes in the parent-child relationship than males [45]. Some studies have found that maltreatment increases the risk of delinquency among females but not among males [46][47][48].…”
Section: The Role Of Gender and Place On Parental Maltreatmentmentioning
confidence: 99%
“…In terms of maintaining gender relations, females are generally supervised more closely than males, and when parental supervision is reduced, females are influenced more negatively than males [45]. The gender of parents can also produce differential rates of parental supervision.…”
Section: The Role Of Gender and Place On Parental Social Controlmentioning
confidence: 99%
“…Crimes against persons occurred least frequently. Others have found vice crimes to be more frequent than property crimes (Covington 1985). In this study, the majority (about 65%) were involved in substance abuse prior to any involvement in criminal acts.…”
Section: Discussionmentioning
confidence: 53%